Reforming teacher education in Nigeria: Laying a foundation for the future. (March 2019) - Barnes, Adrienne E.; Boyle, Helen; Zuilkowski, Stephanie Simmons; Bello, Zaliha Nasiruddeen
Abstract: Teacher educators in Nigeria receive limited professional development, particularly regarding the instruction of early grade reading skills. As part of the USAID-funded Northern Education Initiative Plus project, Florida State University faculty provided intensive teacher educator professional development to staff at four Teacher Education Institutions in northern Nigeria. Positive impacts on teacher educator knowledge, skills, and attitudes were observed related to content and pedagogical knowledge, use of participatory teaching and learning activities in the college classrooms, and improvement in student teacher engagement and learning. Continued success of the implemented model for training will be dependent upon national adoption and scale up. Highlights: Teacher educators in Nigeria lack professional development in teaching reading. FSU supported increased capacity in knowledge, skills, and attitudes related to EGR. Teacher educators are working to incorporate participatory pedagogy into classrooms. Poor infrastructure, lax admission policies, and infrequent PD remain barriers for TEs. Capacity and sustainability will depend on national scale-up of training initiatives.